Synthesis and biological activities of some 4,5-dihydro-1H-1,2,4-triazol-5-one derivatives - (:unkn) unknown (My University, 1998)
Nine new 1,3,4-trisubstituted-4,5-dihydro-1H-1,2,4-triazol-5-ones were synthesized and characterized by elemental analysis, 1H NMR, IR and UV spectra. These new and 30 recently reported 3,4-disubstituted- and 1,3,4-trisubstituted-4,5-dihydro-1H-1,3,4-triazol-5-ones were screened for antibacterial, antitumor and anti-HIV activities.
Keywords: 4,5-dihydro-1H-1,2,4-triazol-5-ones; Antibacterial activity; Antitumor activity; In vitro studies; Synthesis